Evaluation of bacteriological quality of locally produced raw and pasteurised milk in Selangor, Malaysia - Nordin, Yusralimuna; Kwan, Sin Yen; Chang, Wei San; Loo, Yuet Ying; Wan, Tan Chia; Mohd Fadzil, Siti Norshafawatie; Bahumaish, Ramzi Othman Saeed; Kuan, Chee Hao; Premarathne, Krishanthi; Mahmud @ Ab Rashid, Nor Khaizura; New, C. Y.; Radu, Son (Rynnye Lyan Resources, 2019)
High demand for milk has been observed amongst the Malaysian public. Hence, research in milk is essential to assure food safety in milk consumption. This study evaluated the quality of locally-produced milk and present of bacterial hazards in cow and goat milk. A total of 120 milk samples including thirty raw cow milk, thirty pasteurized cow milk, thirty raw goat milk and thirty pasteurised goat milk were collected from dairy farms, delivery milkman, marts and markets in Selangor, Malaysia. The bacteriological quality of milk was evaluated for the presence of Escherichia coli, mesophilic, and coliform bacteria. An acceptable standard limit of < 1 x 105 CFU/mL for the total bacterial count was used to indicate good quality of milk. Overall, all type of milk exceeded 100,000 CFU/mL. The pasteurized raw goat milk showed the highest (7.16 log10 CFU/mL) in total plate count while the pasteurized cow milk recorded as the lowest (5.38 log10 CFU/mL) in total plate count. Approximately half of the milk samples were contaminated with coliform bacteria and a proportion has exceeded the acceptable limit of 50 CFU/mL. The presence of E. coli was detected in over 44% of the samples. Milk contaminated with the pathogenic E. coli can cause self-limited, watery to bloody diarrhea including severe diseases like haemolytic uremic syndrome (HUS). Hence, it is important to ensure the quality of milk for public health safety.